Neuritis retrobulbaris of multiple sclerosis patients - Yu. N. Ignatova; I. V. Smagina; A. O. Gridina; V. A. Sidorenko; A. V. Popovtseva; O. V. Smirnova; S. A. Yelchaninova; A. S. Fedyanin (Бюллетень сибирской медицины, 2009)
According to the anamnesis data 38% of multiple sclerosis patient population had neuritis retrobulbaris as the first clinical symptom. The examination of visual evoked potentials detected that 88% of patients who had suffered from neuritis retrobulbaris earlier, and 19% of those, who had not, had changes revealing possible subclinical demyelinization of a visual nerve.